Bibliometric analysis of functional dyspepsia research trends over the past 20 years - Wang, Xinai; Liu, Hao; Li, Wenjing; Xiao, Hongling (Frontiers in Public Health, 2022)
Background Functional dyspepsia is one of the most common functional gastrointestinal disorders that affects the physical health and quality of life of many people. Its status as a chronic disease has received continued attention in the field of gastrointestinal research. Objective Bibliometric methods using network analysis were used to identify developments and research trends in functional dyspepsia with a view to informing and orienting further in-depth research on functional dyspepsia. Method Bibliometric methods were used to analyze the documents on functional dyspepsia published from 2002 to 2022 retrieved from Web of Science Core Collection on 1 July 2022, import literature data into Excel and VOSviewer, and extract relevant information to analyze and visualize the annual number of publications, authors, organizations, countries, journals published, citations, and keywords. Results A total of 3,532 documents were retrieved, and the abstracts of each remaining documents were read one by one after four duplicate documents were removed, and 2,220 documents were included after screening, with a fluctuating growth trend. Tack J ranked first with 171 documents, followed by Talley NJ (n = 167). The top three organizations in terms of number of publications were Katholieke Universiteit Leuven (n = 131), Mayo Clinic (n = 127), and the University of Newcastle (n = 91). The most prolific country was the United States with 499 documents. The three journals with the highest number of publications are “Neurogastroenterology and Motility” (n = 218), “Alimentary pharmacology & therapeutics” (n = 101), and “Journal of Gastroenterology and Hepatology” (n = 90). The top three most cited documents were “Functional gastroduodenal disorders,” “Childhood Functional Gastrointestinal Disorders: Child/Adolescent,” and “The Serotonin Signaling System: From Basic Understanding to Drug Development for Functional GI Disorders.” Frequency counts and network co-occurrences of keywords reveal trends in this field, including “gastric emptying,” “anxiety,” “acupuncture,” and “ghrelin.” Conclusion The study of the mechanism of gut–brain interaction in functional dyspepsia and the combination of non-pharmacological treatment and pharmacological treatment may be the future research hotspots and trends. Our findings are helpful to comprehensively review the research history of FD and provide reference for researchers in this field to further study.